Macroeconomics : principles, problems, and policies - McConnell, Campbell R. (McGraw-Hill Irwin, 2009)
"The purpose of this supplement is to update selected parts of "Economics", 18e, to account for the U.S. recession that began in December 2007 and worsened toward the end of 2008 ..."--Editor